Beetroot juice and exercise: pharmacodynamic and dose-response relationships - Wylie, Lee J.; Kelly, James; Bailey, Stephen J.; Blackwell, Jamie R.; Skiba, Philip F.; Winyard, Paul G.; Jeukendrup, Asker E.; Vanhatalo, Anni; Jones, Andrew M. (Journal of applied physiology (1985), 2013)
Dietary supplementation with beetroot juice (BR), containing approximately 5–8 mmol inorganic nitrate (NO 3 − ), increases plasma nitrite concentration ([NO 2 − ]), reduces blood pressure, and may positively influence the physiological responses to exercise. However, the dose-response relationship between the volume of BR ingested and the physiological effects invoked has not been investigated. In a balanced crossover design, 10 healthy men ingested 70, 140, or 280 ml concentrated BR (containing 4.2, 8.4, and 16.8 mmol NO 3 − , respectively) or no supplement to establish the effects of BR on resting plasma [NO 3 − ] and [NO 2 − ] over 24 h. Subsequently, on six separate occasions, 10 subjects completed moderate-intensity and severe-intensity cycle exercise tests, 2.5 h postingestion of 70, 140, and 280 ml BR or NO 3 − -depleted BR as placebo (PL). Following acute BR ingestion, plasma [NO 2 − ] increased in a dose-dependent manner, with the peak changes occurring at approximately 2–3 h. Compared with PL, 70 ml BR did not alter the physiological responses to exercise. However, 140 and 280 ml BR reduced the steady-state oxygen (O 2 ) uptake during moderate-intensity exercise by 1.7% ( P = 0.06) and 3.0% ( P < 0.05), whereas time-to-task failure was extended by 14% and 12% (both P < 0.05), respectively, compared with PL. The results indicate that whereas plasma [NO 2 − ] and the O 2 cost of moderate-intensity exercise are altered dose dependently with NO 3 − -rich BR, there is no additional improvement in exercise tolerance after ingesting BR containing 16.8 compared with 8.4 mmol NO 3 − . These findings have important implications for the use of BR to enhance cardiovascular health and exercise performance in young adults.